' … pass the ball … and score the goal man!' An ethnographic perspective of play in the lives of three children. Issue 2 (4th May 2017) - Kinkead-Clark, Zoyah
ABSTRACT: Using ethnographic methodology, the following study examined the role of play in the lives of three children (two boys and one girl) at home and in the community. Two questions guided this study: (1) what does children's play look like, and (2) how do children use play in their lives. In order to answer these questions, observations, semi-structured interviews, collection of field notes and collection of artefacts were used. Three dominant themes emerged from the findings: freedom in play … within limits, play reflects me, and creating a space for me in the world. These findings have implications for: (1) our understanding of child development, (2) parenting programmes and how parents can be encouraged to take advantage of the value of their child's play and (3) government officials and policy-makers and their role in creating physical play spaces for children in communities.